Mengomunikasikan Musik kepada Anak - Azis Taufik Hirzi (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2007)
Musical lessons are believed helping children to nurture their brains. Depended on the beat, rhythm, and melody, music triggers young nerves to develop and stimulates it to reach maximum impact. In the field of communication education, music was involved in learning process. A method called accelerated learning uses music to create conducive and healthy atmosphere which is necessary in learning process. Within such atmosphere, children develop their creativity to solve their problem. Musical lessons help children to develop their personality, effective communication and social interaction capability, and who knows—find their ways to musical talents.